Inflammatory and Nutritional Biomarker in Different Subtypes of Early Stage Diffuse Large B-Cell Lymphoma: Towards a Diagnostic Model - Oehadian A; Gunadi SV; Mersiana L; Susandi E; Wijaya I; Martha JW; Supriyadi R; Prihatni D (Cancer Management and Research)
Amaylia Oehadian,1,* Stephanie Victoria Gunadi,2,* Lusi Mersiana,1 Evan Susandi,2 Indra Wijaya,1 Januar Wibawa Martha,3 Rudi Supriyadi,4 Delita Prihatni5 1Division of Hematology and Oncology Medic, Department of Internal Medicine Faculty of Medicine, Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, Bandung, Indonesia; 2Department of Internal Medicine Faculty of Medicine, Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, Bandung, Indonesia; 3Department of Cardiology and Vascular Medicine Faculty of Medicine, Padjadjaran University, Bandung, West Java, Indonesia; 4Division of Nephrology and Hypertension, Department of Internal Medicine Faculty of Medicine, Padjadjaran University/Hasan Sadikin General Hospital, Bandung, West Java, Indonesia; 5Department of Clinical Pathology Faculty of Medicine, Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, Bandung, Indonesia*These authors contributed equally to this workCorrespondence: Delita Prihatni, Department of Clinical Pathology, Padjadjaran University/ Dr. Hasan Sadikin General Hospital, Jl. Pasteur No. 38, Pasteur, Bandung, West Java, 40161, Indonesia, Email delita.prihatni@unpad.ac.idBackground: Diffuse Large B-Cell Lymphoma (DLBCL) is a heterogeneous malignancy with distinct Germinal Center B-Cell Like (GCB) and non-GCB subtypes. Accurate subtyping is crucial due to differences in prognosis and treatment response. While gene expression profiling is the gold standard, it is often unavailable in low-resource settings. Inflammatory and nutritional biomarkers such as Systemic Immune-Inflammation Index (SII), Prognostic Nutritional Index (PNI), and Advanced Lung Cancer Inflammation Index (ALI) offer a practical alternative. This study aims to evaluate their diagnostic potential in early-stage DLBCL subtypes.Methods: A cross-sectional analysis was conducted on 60 early stage DLBCL patients (30 GCB, 30 non-GCB) at Dr Hasan Sadikin General Hospital Bandung. Clinical characteristics, hematological parameters, and inflammation-based indices (SII, PNI, and ALI) were evaluated. Differences between subtypes were analyzed using the Mann–Whitney U-test, and Receiver Operating Characteristic (ROC) analysis was used to determine diagnostic performance.Results: The median SII was significantly higher in non-GCB compared with GCB (982,575; IQR: 609,112– 2,239,917 vs 575,598; IQR: 454,578– 886,426, p = 0.014). Conversely, PNI was higher in GCB compared to non-GCB group (49.18; IQR: 46.38– 56.38 vs 45.96; IQR 40.05– 52.28, p = 0.011). ALI values were also higher in the GCB than non-GCB (44.14; IQR: 27.69– 67.18 vs 24.51; IQR: 14.34– 42.47,p=0.003). ROC analysis revealed that ALI had the highest diagnostic accuracy (AUC = 0.724; 95% CI: 0.593– 0.831), followed by SII (AUC = 0.685, 95% CI: 0.552– 0.799) and PNI (AUC = 0.691 95% CI: 0.558– 0.804). Optimal cut-off values were ≤ 1,234,133 for SII, > 43.27 for PNI, and > 27.41 for ALI. ALI demonstrated the best balance between sensitivity (76.7%) and specificity (63.3%), making it the most reliable marker for distinguishing DLBCL subtypes.Conclusion: SII, PNI, and ALI differ significantly between DLBCL subtypes. These findings suggest that integrating these indices into a diagnostic model could enhance risk stratification and guide therapeutic decision-making in DLBCL. Further studies with larger cohorts are warranted to validate these findings.Keywords: acute lung inflammation index, ALI, germinal center B-cell like, GCB, non-germinal center B-cell like, Non-GCB, prognostic nutritional index, PNI, systemic immune, inflammation index, SII